7. EFEKTIVITAS ECPAT INDONESIA DALAM MENANGANI KEJAHATAN CHILD SEX TOURISM DI INDONESIA: STUDI KASUS CHILD SEX TOURISM DI BALI TAHUN 2012 -2014 - Rizky Irawan, Noor Fathia; Susiatiningsih, Hermini; Paramasatya, Satwika (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
The crime of child sex tourism in Bali making Indonesia was rated as the country's firstworld sex tourism, it is triggered by a lack of knowledge and lack of strong laws inIndonesia for the offender. Child sex tourism is a threat to children, since the perpetratorsare mostly foreign pedophiles who come on holiday to Indonesia. To overcome thisproblem ECPAT Indonesia undertaking various efforts to assist Indonesia in dealing withchild sex tourism crimes in particular areas of Bali. ECPAT International then make theCode which contains six criteria to be met by the members who are all the hospitality andtourism as a travel agent. The Code has been signed by 41 countries and 1000 companies,as well as implemented in 2012. Unfortunately, in 2012 precisely the number of victims ofchild sex tourism in Bali has increased compared to previous years. The purpose of thisstudy was to determine the effectiveness of the efforts that have been made ECPATIndonesia in dealing with the crime of child sex tourism in Bali in 2012-2014. This type ofresearch is analytic descriptive explanations provide an overview and data development ofchild sex tourism crimes in Bali from year to year as well as the efforts of ECPATIndonesia in dealing with the crime of child sex tourism in Bali in 2012-2014. The resultsobtained from this study is inversely proportional to the hypothesis that had been madepreviously, namely ECPAT Indonesia in dealing with the crime of child sex tourism inBali has not been effective.